KINERJA OMBUDSMAN PERWAKILAN PROVINSI RIAU TAHUN 2012-2014 - ", Nuriyanto; Marta, Auradian (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This study aims to determine how the performance Ombudsman representatives povince Riau in carrying out it’s duties as stipulated in section 7 of law No. 37 of 2008. As for background this study is the high case maladministration in Riau and Ombudsman are expected to provide solutions for the improvement of public service in Riau.This study used descriptive qualitative approach in obtaining and analyzing data, for data analysis, Law No. 37 of 2008 about Ombudsman and law No. 25 of 2009 on publik service the basis for the study of data analysis. As for technique whithdrawal informants done with the approach perposive informants, data in this study was obtained through technique interviews and observation and review of documentation do with some informants those who considered interested and bound in full that concern the researchers As for uses this research is to develop theories the science of government pertaining to the theory public organization and can be beneficial for inputs, and the ideas to ombudsman representatives province Riau to improve their performance.The results shows that Ombudsman representatives province Riau as monitors public service has run his duties by optimal, and by function can do function control to the public service especially in the Riau. As for scope this research including the performance Ombudsman in received reports on suspicion of maladministration in the public service, follow up report covered are divided in space scope of the authority of Ombudsman, conduct an investigation and do efforts to prevent maladministration in the public service .In carrying out duties, Ombudsman representatives provincial Riau in turned to the constraint namely laws and sanctions not firmly, lack of personnel and a budget and lack of public awareness of the existence of Ombudsman in Riau .Keywords: Performance, Duties of Ombudsman and Maladministration